Stroke incidence and anticoagulation treatment in patients with pacemaker-detected silent atrial fibrillation - Sandgren, Emma (PLoS One, 2018)
BACKGROUND: Silent atrial fibrillation (AF) episodes are common but the role of anticoagulation treatment is under debate. METHODS: Consecutive patients with dual-chamber pacemakers for sinus node disease or AV block/bundle branch block were retrospectively enrolled and the development of silent AF, any anticoagulation and the incidence of ischaemic stroke and dementia were recorded. RESULTS: In total 411 patients without and 267 with known AF at implant were included. During a median follow-up of 38 months, 30% (125/411) of patients without known AF at implant were diagnosed with silent AF, 62% of those had or were prescribed anticoagulation. Heart failure (p = 0.03) and age >75 years (p = 0.0002) were risk markers for incident silent AF. In patients with known AF at implant, 80% (216/267) were on anticoagulation at implant. The annual stroke incidence was 2.1% in patients with known AF at implant, as compared to 1.9% in patients who developed silent AF during follow-up, and 1.4% in patients without AF. Vascular dementia developed in 11.2% and 6.2% respectively in patients with known AF versus no AF (p = 0.048) as well as in 5.6% of those with silent AF (p = 0.09) CONCLUSION: The stroke risk in our study population with an incident silent AF diagnosis may have been significantly decreased by the high proportion of anticoagulation treatment. This could imply that without this treatment the stroke risk might have been high enough to justify anticoagulation. Development of vascular dementia was twice as common among patients with known AF as compared to those witht silent AF or no AF. More data is needed to inform the optimal treatment for these patients.